Phylogeny and niche conservatism in North and Central American triatomine bugs (Hemiptera: Reduviidae: Triatominae), vectors of Chagas' disease. - Carlos N Ibarra-Cerdeña; Alejandro Zaldívar-Riverón; A Townsend Peterson; Víctor Sánchez-Cordero; Janine M Ramsey (Public Library of Science (PLoS), 2014)
The niche conservatism hypothesis states that related species diverge in niche characteristics at lower rates than expected, given their lineage divergence. Here we analyze whether niche conservatism is a common pattern among vector species (Hemiptera: Reduviidae: Triatominae) of Trypanosoma cruzi that inhabit North and Central America, a highly heterogeneous landmass in terms of environmental gradients. Mitochondrial and nuclear loci were used in a multi-locus phylogenetic framework to reconstruct phylogenetic relationships among species and estimate time of divergence of selected clades to draw biogeographic inferences. Then, we estimated similarity between the ecological niche of sister species and tested the niche conservatism hypothesis using our best estimate of phylogeny. Triatoma is not monophyletic. A primary clade with all North and Central American (NCA) triatomine species from the genera Triatoma, Dipetalogaster, and Panstrongylus, was consistently recovered. Nearctic species within the NCA clade (T. p. protracta, T. r. rubida) diverged during the Pliocene, whereas the Neotropical species (T. phyllosoma, T. longipennis, T. dimidiata complex) are estimated to have diverged more recently, during the Pleistocene. The hypothesis of niche conservatism could not be rejected for any of six sister species pairs. Niche similarity between sister species best fits a retention model. While this framework is used here to infer niche evolution, it has a direct impact on spatial vector dynamics driven by human population movements, expansion of transportation networks and climate change scenarios.